Pengakuan Formal dan Pemenuhan Hak Nelayan: (Evaluasi Pelaksanaan Kartu Nelayan di Kota Kupang) - Ratumakin, Paulus Adrianus K.L; Kaha, Hendrikus L. (JAP UNWIRA, 2020)
The Fisherman Card as a proof fisherman identity is a form of formal recognition of the existence and rights of the fishermenby the state. The implementation of the fisherman card from Jakarta up to remote areas is regulated in the Decree of theMinister of Marine Affairs and Fisheries No.16 of the year 2016 on the Fisherman Card. The government through theMinistry of Marine Affairs and Fisheries, c.q. the Provincial Office as well as the Municipality Office of Marine Affairsand Fisheries are targeting that the whole fishermen in this area would hold the fisherman card. Since its launching in2013 until the implementation of the Ministerial Regulation on the Fisherman Card, many fishermen have not received thefisherman card while those who hold the card do not understand the function of the card. The Kupang Municipality up to the144JAP UNWIRA, Vol. 1, No. 1, Januari - Juni 2020mid of 2017 has covered only 26.74 percent of the fishermen as card recipients. This research utilizes the Dunn theoreticalframework that covers the aspects of effectiveness, efficiency, adequacy, equality, responsiveness, and correctness to analyze theimplementation of Fisherman Card in Kupang Municipality. The research period that started from June through September2017 in five coastal villages (Nunbaun Sabu, Nunbaun Delha, Pasir Panjang, Oesapa, Lasiana) found that 73.26 percentof the fishermen had not possessed the Fisherman Card. Worse even, the card holders did not understand the purpose of thecard. The low percentage of card ownership is considered as caused by inadequacy of technical apparatus and human resourcesthat could not cover the whole fishermen of Kupang Municipality. The Fisherman Card is also gender-biased in that itaccommodates only fisherman as narrowly defined by the Law No.7 of 2016 as a person whose occupation is catching fish. TheFisherman Card neglects the pre and post activities of fish catching as well as of salt farmers, most of which are female works.The halfhearted recognition by state of the existence of fishermen who are involved in every link of the marine and fisherywork-chain is nothing but an indicator of the state’s absence to fulfill the rights of fishermen, and of fisherwomen in particular.